Inequality Convergence - Ravallion, Martin (World Bank, Washington, DC, 2014)
Comparing changes in inequality with initial levels, using new data, the author finds that within-country inequality in income or per capita consumption is converging toward medium levels--a Gini index around 40 percent. The finding is robust to allow for serially independent measurement error in inequality data and for short-run dynamics around longer-term trends. However, the convergence process is neither rapid nor certain, and more observations over time are needed to be confident of the pattern. The author offers an approach to modeling the determinants of inequality that may be a starting point for estimating richer models.